ChatGPT 101 : supercharge your work and life with ChatGPT. (Packt Publishing, 2023)
ChatGPT is an advanced AI-based conversational agent developed by OpenAI. It is a large language model trained on massive data to understand natural language and generate human-like responses to various questions and prompts. ChatGPT is designed to engage in multiple conversational tasks, from answering general knowledge questions to providing personalized recommendations and advice. This course begins with a brief introduction to ChatGPT and LLMs and delves into tips for success and getting the most out of ChatGPT. It discusses in detail the strengths, weaknesses, restrictions, and limitations of ChatGPT. The importance of verifying information and finding relevant sources is examined. You will learn to create a Notion Swipe File to supercharge our ChatGPT use and different strategies for drafting perfect prompts. We will explore advanced prompt engineering to enhance our outputs and the art of utilizing follow-up prompts. You will learn to tailor prompt outputs to specific voice tones and use context primers to personalize your outputs further. We will explore endless lists of ideas regarding verbs, formats, expert personas, and customer archetypes. Upon completion, you will be adept at using ChatGPT for social media content creation, account growth, and post ideation, and improve efficiency in professional and personal settings. What You Will Learn Explore advanced features and capabilities of ChatGPT Understand the strengths, weaknesses, and limitations of ChatGPT Acquire problem-solving/decision-making skills with ChatGPT predictivity Develop skills to train and fine-tune ChatGPT models for specific apps Understand the ethical/potential risks of using AI in communication Learn advanced AI art and graphics generation (using ChatGPT/MidJourney) Audience This course is designed to be accessible to learners of all levels and caters to professionals and freelancers who are seeking to integrate ChatGPT into their work and personal lives; students looking to upskill and learn how to utilize ChatGPT in their schooling best; and jobseekers looking to leverage the tool to increase their chances of landing their dream career. The prerequisites for the course include a ChatGPT account and the willingness to learn. No coding or technical knowledge is required to complete the course. About The Author Sean Melis: Sean is a seasoned multimodal designer with 15 years of experience, skilled in social media marketing, web design, video production, community management, technology consulting, and conversational AI. As the founder of a successful startup, Bot Hello, he has developed chatbots for renowned brands like Maybelline New York, Lancôme, Anytime Fitness, and Mercedes Benz, and for Australia's largest music festivals, health-food brands, and AFL teams. Sean has worked as an AI consultant for Deloitte. Courier Mail recognized him as a B&T 30 Under 30 Entrepreneur and Top 20 Under 40 Entrepreneur. Sean enjoys helping people understand and utilize tools like ChatGPT, fulfilling their lives and focusing on activities they love.